Steatocystoma multiplex: A review - Manahel Mahmood AlSabbagh (Wolters Kluwer Medknow Publications, 2016)
Steatocystoma multiplex is an uncommon benign disorder typically manifests as multiple asymptomatic intradermal cysts. It can be sporadic, familial or a part of a syndrome. Rare variants can be easily misdiagnosed. Histologically, it appears as an epithelium-lined cystic wall associated with sebaceous lobules. Treatment is needed if symptomatic or for cosmetic issues with the best results reported following radiofrequency, laser therapy and minimally invasive procedures.